PERFIL E PERCEPÇÕES DOS PAIS ADOLESCENTES: UM ESTUDO EXPLORATÓRIO NO MUNICÍPIO DE PONTA GROSSA - PR - Nadal, Isabela Martins (2012)
This research has the objective of identifying the role and perceptions of paternity in adolescence in Ponta Grossa – PR, and it was done over the first semester of 2010. The research started in 2009 in the Applied Social Sciences Master Course – UEPG, for which the main focus was to investigate the paternity in adolescence and its effects. The main objectives were to quantify and classify adolescent fathers in Ponta Grossa, and identify the changing in their lives after paternity. In the case of the present study the subjects were teenage fathers and mothers, and the universe of the research involved 42 (forty-two) Health Care Units in Ponta Grossa – PR. This work is structured in two chapters. The first chapter is about bibliographic review of the roles, pregnancy in youth and family. The second chapter brings a teenage pregnancy outlook in Ponta Grossa, some features of the teenage fathers and it offers for consideration interviews with the selected individuals through a selection of data gathered from the town´s childcare database. It was a quantitative and qualitative research, in which the selection of data was through semi-structured interviews subsequently the Content Analysis in order to reflect upon the empirical and theoretical data.